New record of Gonatophragmium mori (Sawada) Deighton on Ficus hispida L. from Bangladesh (Bangladesh Journal of Plant Taxonomy, 2017)
Not available.Keywords: Gonatophragmium mori; Hyphomycetes; Ficus hispida L.; New record.Bangladesh J. Plant Taxon. 24(1): 125127, 2017 (June)